Awakening Giants, Feet of Clay : Assessing the Economic Rise of China and India - Bardhan, Pranab K. (Book collections on Project MUSE., 2013)
"The recent economic rise of China and India has attracted a great deal of attention. Yet, many of the views regarding their market reforms and high growth have been tendentious, exaggerated, or oversimplified. Awakening Giants, Feet of Clay scrutinizes the phenomenal rise of both nations and demolishes the myths that have accumulated around the economic achievements of these two giants in the last quarter-century. Exploring the challenges that both countries must overcome to become true leaders in the international economy, Pranab Bardhan looks beyond short-run macroeconomic issues to examine structures, and current general performance. Full of valuable insights, Awakening Giants, Feet of Clay provides a nuanced picture of China and India's complex political economy at a time of startling global reconfiguration and change."--Provided by publisher.